The Role of Price Discounts in Moderating, Customer Reviews and Free Shipping on Shopee Purchase Decisions in Surabaya - Muhammad Rosyihuddin; Joni Hendra (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2022)
Abstract: Along with technological developments, the world of marketing has now changed. Studying E-consumer behavior from a renewable aspect is needed to create practical and efficient marketing, research that refers to digital marketing (Digital Marketing), especially the E-Marketing marketplace. This study examines online consumer behavior that focuses on purchasing decisions and renewable factors that influence it, namely: customer reviews and the promotional tagline "Free Shipping" for shopee marketplace consumers in Surabaya. The chosen mediator variable is Price Discount. The sample in this study was 100 respondents from Surabaya, East Java, Indonesia. The analytical tool used is mediation analysis using the SmartPLS 3.5 tool. The hypothesis was investigated using customer reviews, promotional taglines, price discounts, and promotional taglines on e-purchase decisions mediated by price discounts. Based on the analysis results, all the tested hypotheses have a positive and significant effect on the E-Purchase Decision. The Price Discount variable is a mediator variable that can strengthen the Tagline Promotion variable in the E-Purchase Decision. This finding is expected to make a real contribution for sellers in the marketplace at Shopee to pay attention to Customer Reviews so that consumers don't give negative feedback to their online stores. Always provide free shipping promos so that consumers are not burdened with purchasing costs. The discount can benefit consumers and pay attention to the mediator variables studied so that consumers who buy are more likely to buy the product.